2019
DOI: 10.1085/jgp.201812143
|View full text |Cite
|
Sign up to set email alerts
|

Agonists that stimulate secretion promote the recruitment of CFTR into membrane lipid microdomains

Abstract: Little is known about how CFTR, the Cl− channel that is mutated in cystic fibrosis, interacts with lipids. Abu-Arish et al. show that agents that stimulate salt and fluid secretion reduce CFTR lateral mobility and promote its clustering into ceramide-rich platforms, thereby increasing its surface expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 80 publications
2
51
1
Order By: Relevance
“…The effects of altered membrane microdomain abundance on relative fluidity and stability of transmembrane receptors involved in inflammatory responses and activity of ion channels remains poorly understood (15,45,46). Notably, Abu-Arish and colleagues recently demonstrated that epithelial cells respond to secretagogues by forming clusters of CFTR in ceramide-rich membrane microdomains via an acid sphingomyelinase-dependent mechanism to increase transepithelial secretion (47). We found that reducing ceramide in CF epithelial cells, via rhAC treatment, was associated with reduced TNFR1 expression, decreased cRel nuclear localization, and less IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of altered membrane microdomain abundance on relative fluidity and stability of transmembrane receptors involved in inflammatory responses and activity of ion channels remains poorly understood (15,45,46). Notably, Abu-Arish and colleagues recently demonstrated that epithelial cells respond to secretagogues by forming clusters of CFTR in ceramide-rich membrane microdomains via an acid sphingomyelinase-dependent mechanism to increase transepithelial secretion (47). We found that reducing ceramide in CF epithelial cells, via rhAC treatment, was associated with reduced TNFR1 expression, decreased cRel nuclear localization, and less IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 5 years, several studies have investigated the role of lipid composition and dynamics of the plasma membrane in the trafficking of cystic fibrosis (CF) transmembrane conductance regulator (CFTR), the anion transporter defective in CF. The role of cholesterol and ceramides, including short-chain ones (1), in the formation of CFTR clusters in the plasma membrane has been reported (2), as well as the stabilization of CFTR triggered by phosphatidylserines (3). An important contribution to CFTR stability at the cell membrane also comes from the action of flippases (4), enzymes known to regulate the movement of phospholipids across the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this study, cholesterol was only thought to act indirectly rather than directly to regulate the function of CFTR. According to a recent study by Hanrahan and colleagues, secretagogues, like vasoactive intestinal peptide acted to promote association of CFTR with cholesterol-containing clusters on the apical surface of respiratory epithelial cells [57]. This clustering restricts the lateral mobility of CFTR, thereby enabling its efficient incorporation into macromolecular complexes important for phosphorylation-dependent regulation and integration with larger, ceramide rich platforms [57].…”
Section: Discussionmentioning
confidence: 99%